2020
DOI: 10.1080/20009666.2020.1781349
|View full text |Cite
|
Sign up to set email alerts
|

Man vs. man-made marijuana: A case of drug-induced posterior reversible encephalopathy syndrome (PRES) due to K2, a synthetic cannabinoid (SCB)

Abstract: Synthetic Cannabinoids (SCB) are engineered chemical compounds that share a similar chemical structure with the active ingredient of marijuana, delta-9-tetrahydrocanabinol. Although the FDA has not approved the use of SCB without a prescription from a licensed health-care provider, the cost effectiveness and availability of SCB has made it a popular choice among recreational drug users. Manufacture of SCB as a street drug is not regulated. These SCB are highly potent chemicals that cause various severe toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…157 CB1 receptor activation may decrease cerebral blood flow, 159 with ischemia noted in the posterior circulation that can mimic signs of posterior reversible encephalopathy syndrome (PRES) in the postpartum period. 160…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…157 CB1 receptor activation may decrease cerebral blood flow, 159 with ischemia noted in the posterior circulation that can mimic signs of posterior reversible encephalopathy syndrome (PRES) in the postpartum period. 160…”
Section: Original Researchmentioning
confidence: 99%
“…84 Strong CB1 agonism (or synthetic cannabinoid (eg, 'K2'/'spice') may lead to or be associated with preeclampsia use may cause or be associated with symptoms resembling preeclampsia, cerebral ischemia, or PRES. 160 Long-term cannabinoid exposure may cause a cross tolerance to opioids and require greater use of opioids. 124 176 Acute intoxication with cannabinoids may augment the analgesia of mu and kappa opioid agonists, thus potentially reducing the dosage requirement for opioids.…”
Section: Intrapartum Anesthetic Considerationsmentioning
confidence: 99%
“…There is no direct connection between the serum levels of immunosuppressive medication and the development of PRES [ 14 ]. Few cases of PRES are be related to consumption of alcohol [ 15 ], cocaine [ 16 ], mephedrone [ 17 ], kratom [ 18 ], and K2 [ 3 ] have been reported in the literature. We report the second case of PRES caused by consumption of K2.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, among a cohort of college students, it was found that the weighted lifetime prevalence of K2 use at college entry was 7.6% [ 2 ]. Synthetic cannabinoids (SCBs) are increasingly gaining popularity as they are cheaper and are not detected by most standard drug screens [ 3 ]; therefore, its use is more common among low income individuals and high school and college students. K2 can be smoked using joints, pipes, and E-Cigarettes, or it can be brewed as a tea.…”
Section: Introductionmentioning
confidence: 99%
“…A few case reports show that SCRA users can develop autoimmune disease ( 22 , 23 ). The study by Parajuli et al represents a case about a drug-induced posterior reversible encephalopathy syndrome (PRES) after K2 consumption (a type of SCRAs); besides, the autoimmune mechanism of a toxic origin can be found in the background of PRES ( 24 ). Furthermore, in our previous study, we reported the case of a teenager who used SCRA and was diagnosed with NMDA encephalitis ( 16 ).…”
Section: Introductionmentioning
confidence: 99%